The value of intratumoral and peritumoral radiomics features based on multiparametric MRI for predicting molecular staging of breast cancer - Han, Yuxuan; Huang, Manxia; Xie, Lizhi; Cao, Yuhai; Dong, Yang (Frontiers in Oncology, 2025)
PurposeA model for preoperative prediction of molecular subtypes of breast cancer using tumor and peritumor radiomics features from multiple magnetic resonance imaging (mMRI) sequences, combined with semantic features.Materials and methodsA total of 254 female patients with pathogically confirmed breast cancer were enrolled in this study. Preoperative mMRI, including T2-weighted imaging (T2WI), diffusion-weighted imaging (DWI), and dynamic contrast-enhanced MRI (DCE) sequences, covered the entire breast. To analyze the MRI semantic features of different molecular subtypes of breast cancer and identify independent predictive risk factors. Thirty-three binary classification models were established based on the radiomic features of different sequences and peritumoral ranges. The best radiomics model was selected by comparing the performance of the above radiomics models. At the same time, the best sequence and peritumoral extent were extracted from the target features, the radiomics score was calculated, and independent risk factors were predicted. Finally, a nomogram was established for preoperative prediction of Triple-Negative Breast Cancer (TNBC), Hormone Receptor (HR) positive and HER2 negative (HR+/HER2−), and HER2+ molecular staging types of breast cancer.ResultsTumor length, edge enhancement, and peritumoral edema were independent risk factors for predicting the different molecular types of breast cancer. The best MRI sequence was DCE and the best peritumoral margin was 6 mm. The AUC of the nomogram based on the optimal sequence(DCE) and optimal peritumoral range (6 mm) combined with independent risk factors were 0.910, 0.909, and 0.845, respectively.ConclusionThe nomogram based on independent predictors combined with intratumoral and peritumoral radiomics scores can be used as an auxiliary diagnostic tool for molecular subtype prediction in breast cancer.